Development of Asset Management Control Application for Direktorat Jenderal Sumber Daya dan Perangkat Pos dan Informatika - Richard Richard (Bina Nusantara University, 2017)
The purpose of this research was to identify problems, analyze needs, and develop management information system especially the process internal control of asset management on Direktorat Jenderal Sumber Daya dan Perangkat Pos dan Informatika (SDPPI - government communication and informatics organization). This system development used the System Development Life Cycle (SDLC) method which refers to 4 phases. Those were initiation and business feasibility, requirements definitions, functional design, and verification. The analysis used to support the research methods was Enterprise Architecture (EA) and SWOT. The analysis was conducted on business process that was running at the moment. The results show that the management information system in the form of web-based applications can help the process based on activity logging assets, assets allocation, complaints, and user guide in accordance with the needs of the Direktorat Jendral SDPPI. The design of this application can also help the existing asset management process to become more efficient and effective.